Evaluation of Knowledge of Dentists Working in Dental Clinics in Tobruk City Regarding Radiation Protection - Yosef Madee; Nagwa Bochwal; Aybaba Hançerlioğulları (AlQalam Journal of Medical and Applied Sciences, 2025)
About 20% of radio diagnostics in dental radiology represents human radiation exposure. Although the radıatıon dose of intraoral dentistry is low, however cannot be ignored due to the procedures performed. This study was carried out to evaluate the knowledge of dentists towards radiation hazards and protection. The data collected through questionnaires of 10 questions and analyzed by using Microsoft Excel software. The knowledge was limited among dentists. 70 % of dentists used a rectangular collimator, and 30% used a circular collimator. The type of films used by 90% of dentists were E-speed films, and 10% dentists used D-speed film. 80 % of dentists were not using film holders and asked their patients to hold the films inside the mouth with their fingers for almost every exposure. Lead aprons were worn by 30% of dentists during exposure, and 70% did not use any type of lead apron. 20 % of dentists use monitoring, and 80 % of dentists do not use any type of radiation monitoring devices. The study showed that dentists’ awareness and knowledge are poor about radiation protection; as a result, all dentists need training programs in radiation protection.